The influence of boron nitride shape and size on thermal conductivity, rheological and passive cooling properties of polyethylene composites - Wang, Yiding; Zhang, Wenrui; Feng, Mingjie; Qu, Muchao; Cai, Zhenghao; Yang, Guanda; Pan, Yamin; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Composites Part A-Applied Science and Manufacturing, 2022)
The shape and particle size of the filler are highly relevant to the composite's performance and application. We herein report the role of boron nitride (BN) shapes and sizes for polyethylene composites on the rheological properties, thermal conductivity (TC) and passive cooling via melt blending. Fillers with large sizes are adverse to form a rheological network in the composites, but they are beneficial to high thermal conductivity and their maximum increase (1.535 Wm−1K−1) relative to the matrix is 256%. Additionally, due to the high solar reflectance (90%) and thermal emittance (85%), the composites endow a cooling performance of 4 °C at daytime and 10 °C at night compared to the contrast temperature in the device. This work is helpful to provide guidance for the optimization of BN fillers for applications in the fields of thermal management and passive cooling.
CRIS-Team Scopus Importer:2022-08-12
Keywords: A. Polymer-matrix composites (PMCs); B. Rheological properties; B. Thermal properties; Passive cooling